2015
DOI: 10.1002/mnfr.201500595
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin suppresses immune cell accumulation and improves mitochondrial gene expression in adipose tissue of diet‐induced obese mice

Abstract: ScopeTo examine the effect of dietary quercetin on the function of epididymal adipose tissue (EAT) in Western diet‐induced obese mice.Methods and resultsC57BL/6J mice were fed a control diet; a Western diet high in fat, cholesterol, and sucrose; or the same Western diet containing 0.05% quercetin for 18 weeks. Supplementation with quercetin suppressed the increase in the number of macrophages, the decrease in the ratio of CD4+ to CD8+ T cells in EAT, and the elevation of plasma leptin and tumor necrosis factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 47 publications
2
78
0
1
Order By: Relevance
“…It has been known as a multifactorial and progressive disease [1,3,30]. The dietary flavonoid quercetin is thought to promote health, partly due to its ability to act as an anti-inflammatory and antioxidant against ROS properties [15][16][17][18]. Consistent with previous studies, high doses of quercetin, especially at the 100 mg/kg, in our study showed similar effects on suppression of inflammation, apoptosis and oxidative stress [19,31].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It has been known as a multifactorial and progressive disease [1,3,30]. The dietary flavonoid quercetin is thought to promote health, partly due to its ability to act as an anti-inflammatory and antioxidant against ROS properties [15][16][17][18]. Consistent with previous studies, high doses of quercetin, especially at the 100 mg/kg, in our study showed similar effects on suppression of inflammation, apoptosis and oxidative stress [19,31].…”
Section: Discussionsupporting
confidence: 94%
“…Quercetin has beneficial effects on human health for its broad pharmacological properties, such as anti-inflammation and anti-oxidation [15,16]. In addition, quercetin down-regulated serum leptin and insulin levels, ameliorating leptin and insulin resistance via regulation of leptin and insulin signaling in the cell or tissue of animals [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kim et al [14] reported that quercetin-rich OPE supplementation increased the adiponectin production at a transcription level in the high fat diet-induced obese animal model, suggesting that quercetin-rich OPE has modulatory effect on the inflammatory processes in obesity. Furthermore, quercetin increased levels of secreted adiponectin in TNF-α-treated 3T3-L1 adipocytes [25] as well as in obese Zucker rats [8] and diet-induced obese mice [26]. In the present study, adiponectin levels in placebo and OPE-treated groups were increased compared with baseline values.…”
Section: Discussionsupporting
confidence: 50%
“…The concentration of leptin is increased in inflammatory conditions in animal model [3031] and in rheumatoid arthritis patients [32]. In animal model, quercetin reduced both plasma leptin and expression of leptin in adipose tissue from mice fed the Western diet for 18 weeks [26]. However, we observed that neither placebo nor OPE supplementation significantly changed the concentration of leptin.…”
Section: Discussionmentioning
confidence: 89%
“…In one study, QR increased levels of secreted adiponectin in tumor necrotising factor (TNF)-α-treated 3T3-L1 adipocytes (28) as well as in diet-induced obese rats (29). Furthermore, Kim et al (14) reported that quercetinrich onion peel extract (OPE) supplementation increased the transcriptional level of adiponectin expression in the high-fat diet-induced obese rats, suggesting that quercetin-rich OPE has modulatory effect on the inflammatory processes in obesity.…”
Section: Discussionmentioning
confidence: 99%